A Molecular Survey of Bacterial Species in the Guts of Black Soldier Fly Larvae (Hermetia illucens) Reared on Two Urban Organic Waste Streams in Kenya - Shumo, Marwa; Khamis, Fathiya M.; Ombura, Fidelis Levi; Tanga, Chrysantus M.; Fiaboe, Komi K. M.; Subramanian, Sevgan; Ekesi, Sunday; Schlüter, Oliver K.; van Huis, Arnold; Borgemeister, Christian (Frontiers in Microbiology, 2021)
Globally, the expansion of livestock and fisheries production is severely constrained due to the increasing costs and ecological footprint of feed constituents. The utilization of black soldier fly (BSF) as an alternative protein ingredient to fishmeal and soybean in animal feed has been widely documented. The black soldier fly larvae (BSFL) used are known to voraciously feed and grow in contaminated organic wastes. Thus, several concerns about their safety for inclusion into animal feed remain largely unaddressed. This study evaluated both culture-dependent sequence-based and 16S rDNA amplification analysis to isolate and identify bacterial species associated with BSFL fed on chicken manure (CM) and kitchen waste (KW). The bacteria species from the CM and KW were also isolated and investigated. Results from the culture-dependent isolation strategies revealed that Providencia sp. was the most dominant bacterial species detected from the guts of BSFL reared on CM and KW. Morganella sp. and Brevibacterium sp. were detected in CM, while Staphylococcus sp. and Bordetella sp. were specific to KW. However, metagenomic studies showed that Providencia and Bordetella were the dominant genera observed in BSFL gut and processed waste substrates. Pseudomonas and Comamonas were recorded in the raw waste substrates. The diversity of bacterial genera recorded from the fresh rearing substrates was significantly higher compared to the diversity observed in the gut of the BSFL and BSF frass (leftovers of the rearing substrates). These findings demonstrate that the presence and abundance of microbiota in BSFL and their associated waste vary considerably. However, the presence of clinically pathogenic strains of bacteria in the gut of BSFL fed both substrates highlight the biosafety risk of potential vertical transmission that might occur, if appropriate pre-and-postharvest measures are not enforced.